ACTIVITIES OF THE FIRST LADIES OF THE WORLD'S LEADING COUNTRIES THROUGH THE PRISM OF SOFT POWER - Hapak, Nataliia (Collection of scientific papers «ΛΌГOΣ», 2023)
The term "soft diplomacy of the first lady" was coined by the Chinese media when journalists reported on Peng Liyuan and her colleague Michelle Obama. They are considered to be the women who most actively shape soft power .